PENGARUH PENGGUNAAN LETHAL OVITRAP TERHADAP POPULASI NYAMUK AEDES SP SEBAGAI VEKTOR DEMAM BERDARAH DENGUE - Tri Ramadhani; Bondan Fajar Wahyudi (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2013)
ABSTRACT. Field evaluation against lethal ovitrap (LO) to control dengue vector Aedes mosquitoes carried intwo endemic areas (Bojongsari and Ledug) in Banyumas. Lethal ovitrap made ?with the intent to kill mosquito,because mosquitoes will lay eggs containing ovistrip contact with the insecticide and the relatively short time todie.The aim of research to assess the effect of LO applications with the Aedes of mosquito populations sp. Thisstudy includes a quasi experimental design with pretest-posttest control group without randomization. Researchsites in dengue endemic areas with a total sample of 100 houses in each treatment and control areas. Populationsof Aedes sp measured every week for three weeks prior to the intervention and twelve weeks during theintervention. The mean density of Aedes sp compared before and after intervention and between the treatment andcontrol. Results showed mean mosquito density before and after the intervention in the treatment group of 0.07(p-value 0.044), whereas in the control group by 0037 ( p-value 0341). Use LO made ?with the addition ofinsecticide active cypermetrin on ovistrip impact on the density of Aedes sp in the residential neighborhood.